Genetic and Epigenetic Consequence of Early-Life Social Stress on Depression: Role of Serotonin-Associated Genes - Soga, Tomoko; Teo, Chuin Hau; Parhar, Ishwar (Frontiers in Genetics, 2021)
Early-life adversity caused by poor social bonding and deprived maternal care is known to affect mental wellbeing and physical health. It is a form of chronic social stress that persists because of a negative environment, and the consequences are long-lasting on mental health. The presence of social stress during early-life can have an epigenetic effect on the body, possibly resulting in many complex mental disorders, including depression in later life. Here, we review the evidence for early-life social stress-induced epigenetic changes that modulate juvenile and adult social behaviour (depression and anxiety). This review has a particular emphasis on the interaction between early-life social stress and genetic variation of serotonin associate genes including the serotonin transporter gene (5-HTT; also known as SLC6A4) which are key molecules involved in depression.